2021
DOI: 10.4102/hsag.v26i0.1643
|View full text |Cite
|
Sign up to set email alerts
|

Interactive workshops as a learning and teaching method for primary healthcare nurses

Abstract: Background: Traditionally, learning by and teaching for primary healthcare (PHC) nurses use didactic, teacher-centred approaches. Hence, the feasibility of interactive workshops in non-threatening PHC environments to refresh nurses’ knowledge on patient care needs exploring.Aim: To describe interactive workshops as a learning and teaching method for PHC nurses.Setting: Primary healthcare clinics.Methods: Systematic literature search followed by an exploratory experimental pre or post-test control group design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…This observation aligns with the findings of previous studies involving non-health professionals, where it was found that training workshops enhanced the oral health knowledge of school teachers [25,26]. Although interactive workshops could improve knowledge and participant satisfaction, combining interactive workshops with other teaching methods may be more successful [27]. Based on our findings, among the various educational methods and materials, CDs were reported to be the least utilized.…”
Section: Discussionsupporting
confidence: 91%
“…This observation aligns with the findings of previous studies involving non-health professionals, where it was found that training workshops enhanced the oral health knowledge of school teachers [25,26]. Although interactive workshops could improve knowledge and participant satisfaction, combining interactive workshops with other teaching methods may be more successful [27]. Based on our findings, among the various educational methods and materials, CDs were reported to be the least utilized.…”
Section: Discussionsupporting
confidence: 91%
“…While scenariobased simulations can be used when time and personnel constraints are not a concern [51,52], the combination of simulation training and virtual simulations can improve the time and cost-effectiveness of education/training. However, the adoption of virtual simulation education/ training platforms requires careful consideration of technological and platform-related issues [44,[53][54][55]. On the other hand, the discussion method focuses on developing trainees' problem-solving skills and analytical judgment, but it demands a high level of trainer experience and skill [54].…”
Section: Country Of Published Work [Reference List Id]mentioning
confidence: 99%
“…However, the adoption of virtual simulation education/ training platforms requires careful consideration of technological and platform-related issues [44,[53][54][55]. On the other hand, the discussion method focuses on developing trainees' problem-solving skills and analytical judgment, but it demands a high level of trainer experience and skill [54]. In the context of stroke education and training, a comprehensive approach, combining classroom lectures, simulation training, and discussion methods, is recommended to ensure a better translation of theoretical knowledge of stroke management into clinical practice in future education and training programs.…”
Section: Country Of Published Work [Reference List Id]mentioning
confidence: 99%